2016
DOI: 10.11606/issn.2176-7262.v49i3p248-257
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization, deaths, expenses respiratory diseases and its relationship with climate change in the municipality of San Carlos - SP, Brazil

Abstract: Modelo do estudo: Estudo ecológico de séries temporais. Objetivos: Descrever as internações hospitalares, óbitos e custos com as doenças respiratórias (DR) e verificar suas relações com as alterações climáticas. Métodos: Dados anuais e mensais foram coletados do registro de autorização de internação hospitalar (AIH) e óbitos do Departamento de Informática do Sistema Único de Saúde, fornecidos pelo Sistema de Informações Hospitalares do SUS, no período de 2008 a 2012, que incluíram o número de AIH, óbitos e cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
1
Order By: Relevance
“…More than half of the studies use simulation methods such as Computable General Equilibrium (CGE), Integrated Assessment Models of Climate Change (e.g., FUND model), Life-Cycle Assessment (LCA), uncertainty propagation methods, Disability Life Years Lost (DALYs), among others. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 , 39 , 39 These models estimate baseline scenarios (or business-as-usual) and compare them to simulated policy scenarios, changes in technology, or other counterfactual scenarios to examine how climate change, deforestation rates, or carbon dioxide (CO 2 ) emissions impact economic outcomes through changes in health, land use patterns or other channels. For example, the Climate Framework for Uncertainty, Negotiation, and Distribution (FUND) model explicitly assesses the health cost contribution to estimates of the social cost of carbon dioxide (SC-CO 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More than half of the studies use simulation methods such as Computable General Equilibrium (CGE), Integrated Assessment Models of Climate Change (e.g., FUND model), Life-Cycle Assessment (LCA), uncertainty propagation methods, Disability Life Years Lost (DALYs), among others. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 , 39 , 39 These models estimate baseline scenarios (or business-as-usual) and compare them to simulated policy scenarios, changes in technology, or other counterfactual scenarios to examine how climate change, deforestation rates, or carbon dioxide (CO 2 ) emissions impact economic outcomes through changes in health, land use patterns or other channels. For example, the Climate Framework for Uncertainty, Negotiation, and Distribution (FUND) model explicitly assesses the health cost contribution to estimates of the social cost of carbon dioxide (SC-CO 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most use Ordinary Linear Squares (OLS) and time series analyses. 21 , 23 , 24 , 25 , 31 , 33 Others use Linear Probability Models (LPM) or Probit Models to predict the probabilities of the occurrence of specific outcomes. 24 , 26 Only two articles properly identify a causal relationship between climate risks (e.g., droughts, extreme rainfall and temperature) and human health, labour productivity, or welfare outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the city of São Carlos, Cruz et al [58] proved a relationship between the increased hospital admissions due to respiratory diseases and climate change for 2008-2012. Natali et al [59] suggested that the increased number of hospitalization cases in children and adolescents due to pneumonia in São Paulo between summer and autumn was because of pollutant emissions.…”
Section: Rainfall Effectmentioning
confidence: 99%
“…As doenças respiratórias, como pneumonia, Doença Pulmonar Obstrutiva Crônica (DPOC), bronquite e bronquiolite aguda, e asma, são responsáveis pelos maiores índices de internação hospitalar e óbitos, gerando altos custos para os serviços de saúde 1 . Segundo dados da Organização Mundial da Saúde (OMS), estima-se que 251 milhões de pessoas no mundo tenham o diagnóstico de DPOC, sendo esta a terceira principal causa de mortalidade no mundo 2 .…”
Section: Introductionunclassified